2020
DOI: 10.1029/2020ja028620
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Case of Complex Interaction Between MSTIDs and Mid‐Latitude Field‐Aligned Plasma Depletions Over Geomagnetic Low‐Mid Latitude Transition Region

Abstract: On a geomagnetically quiet night of July 07, 2018, the allsky imager at Hanle, Leh Ladakh (32.7°N, 78.9°E; Mlat. ∼24.1°N), India captured a number of plasma structures in O (1D) 630.0 nm airglow emission. In a short observational period of around 3 h, two different medium scale traveling ionospheric disturbances and two different mid‐latitude plasma depletions were observed. The most interesting aspect of the night was the drastic difference in the behavior of the two plasma depletions, which simultaneously ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It is thus extremely rare for an EMSTID that directly encounters an EPB. Yadav et al (2021) recently reported a unique case of a complex interaction between EMSTIDs and mid-latitude field-aligned plasma depletions over the geomagnetic low-mid latitude transition regions of India. However, either an extended part of the EMSTID or an EPB depletion could be the source of those mid-latitude field-aligned plasma depletions in their study.…”
mentioning
confidence: 99%
“…It is thus extremely rare for an EMSTID that directly encounters an EPB. Yadav et al (2021) recently reported a unique case of a complex interaction between EMSTIDs and mid-latitude field-aligned plasma depletions over the geomagnetic low-mid latitude transition regions of India. However, either an extended part of the EMSTID or an EPB depletion could be the source of those mid-latitude field-aligned plasma depletions in their study.…”
mentioning
confidence: 99%
“…In all the cases, the polarization electric field within the MSTIDs' fronts played a role in the interaction process. Of late, simultaneous existence of two different MSTIDs has been reported from the same location of Hanle (Rathi et al., 2021; Yadav, Rathi, Sarkhel, et al., 2021), but in these cases, there was no interaction between these coexisting MSTIDs. Wu et al.…”
Section: Discussionmentioning
confidence: 97%
“…MSTIDs, plasma bubbles, etc. in the F region over midlatitudes (Otsuka et al., 2012; Rathi et al., 2021; Wu et al., 2021; Yadav, Rathi, Gaur, et al., 2021; Yadav, Rathi, Sarkhel, et al., 2021). Still fewer studies have reported interaction between such coexisting plasma structures (Otsuka et al., 2012; Wu et al., 2021; Yadav, Rathi, Gaur, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2021), and Yadav, Rathi, Sarkhel, et al. (2021) observed a mid‐latitude spread‐F/field aligned plasma structures over the low‐mid‐latitude transition region, Hanle and argued the possible supporting mechanism. However, to the best of our knowledge, there is no observational evidence that shows the onset and evolution of plasma depletion in the FOV of an airglow imager over the geomagnetic low‐mid latitude transition region.…”
Section: Discussionmentioning
confidence: 98%